Transport of sugars contained in an ionic liquid medium via a supported liquid membrane - Tharaka Ruwan Bandara; Gregory John Griffin (Journal of Ionic Liquids, 2022)
Bioethanol, an accepted substitute for petroleum-based fuels, can be produced from lignocellulosic biomass. Ionic liquid pretreatment of biomass has gained popularity as it can dissolve both hemicellulose and cellulose, which enhances hydrolysis to monosaccharides. The resulting monosaccharides need to be separated from the ionic liquid and other constituents, such as lignin, which inhibit fermentation when producing bioethanol. Experiments were designed to selectively transport glucose and xylose in a synthetic aqueous ionic liquid solution (the departure phase) via a supported liquid membrane. The ionic liquid used was 1-ethyl-3-methylimidazolium acetate. The monosaccharides were transported to an aqueous neutral receiving phase. The polypropylene membrane separating the departure and receiving phases was impregnated with phenylboronic acid and/or Aliquat 336 extractant(s) dissolved in a diluent (2-nitrophenyl octyl ether). It was found that it is technically feasible to selectively transport sugars from an IL medium, via a SLM, enabling both IL recovery and producing purified sugar solutions for potential subsequent fermentation to produce ethanol. The transport flux was found to be higher when the ionic liquid in the departure phase was mixed with an alkaline solution compared with neutral water. Xylose was transported at greater rates than glucose from equi-molar solutions in the departure phase. However, a phenyl boronic acid/Aliquat 336 combination decreased extraction when compared to extraction using Aliquat 336 alone. This inhibitory effect of phenyl boronic acid was unexpected as extraction and transport of monosaccharides from aqueous solutions is enhanced when phenyl boronic acid is added to Aliquat 336. When Aliquat 336 was the lone extractant, increasing concentration linearly increased the extraction and transport rate of both sugars with maximum transport rates of 2.324 mmol.m−2.h−1 for xylose and 0.942 mmol.m−2.h−1 for glucose. Although the transport of sugars was selective, rates were slow, so recovery of sugars was small.